2021
DOI: 10.1029/2020gl091235
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Tropical Response to Recent Observed Southern Ocean Cooling?

Abstract: Despite global warming, SSTs in the Southern Ocean (SO) have cooled in recent decades largely as a result of internal variability. The global impact of this cooling is assessed by nudging evolving SO SST anomalies to observations in an ensemble of coupled climate model simulations under historical radiative forcing, and comparing against a control ensemble. The most significant remote response to observed SO cooling is found in the tropical South Atlantic, where increased clouds and strengthened trade winds co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 57 publications
3
28
0
Order By: Relevance
“…However, remote influences from other regions may also play a role (Krishnamurthy & Krishnamurthy, 2016). For example, the Southern Ocean (Zhang et al, 2021), South Atlantic (Xue et al, 2018), extratropical Pacific (Krishnamurthy & Krishnamurthy, 2016), and the North Atlantic Oscillation (Xie et al, 2021) may contribute to the Indian Ocean multidecadal variability. We also notice that current climate models (e.g., CESM1) tend to overestimate the magnitude of the SST variability in the southeastern Indian Ocean, which implies that the models may not realistically simulate the decadal to multidecadal variations (Kravtsov et al, 2018;Mann et al, 2020) or inter-basin teleconnection (Cai et al, 2019;Li et al, 2016) for the Indian Ocean.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, remote influences from other regions may also play a role (Krishnamurthy & Krishnamurthy, 2016). For example, the Southern Ocean (Zhang et al, 2021), South Atlantic (Xue et al, 2018), extratropical Pacific (Krishnamurthy & Krishnamurthy, 2016), and the North Atlantic Oscillation (Xie et al, 2021) may contribute to the Indian Ocean multidecadal variability. We also notice that current climate models (e.g., CESM1) tend to overestimate the magnitude of the SST variability in the southeastern Indian Ocean, which implies that the models may not realistically simulate the decadal to multidecadal variations (Kravtsov et al, 2018;Mann et al, 2020) or inter-basin teleconnection (Cai et al, 2019;Li et al, 2016) for the Indian Ocean.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It has also been suggested that observed trends in the Southern Ocean could result from an anomalous phase of Southern Ocean multi-decadal variability (e.g., L. Zhang et al (2019)). This remains plausible, though its relevance for lower latitude SST trends depends on an active body of work to quantify the teleconnections from Southern Ocean SST changes (Dong et al, 2022;Hwang et al, 2017;Kang et al, 2019;Kim et al, 2022;X. Zhang et al, 2021).…”
Section: Possible Interpretationsmentioning
confidence: 99%
“…The latest generation of coupled climate models in the Climate Model Intercomparison Project Phase 6 (CMIP6; Eyring et al., 2016) generally does not capture the observed Southern Ocean cooling nor Antarctic sea ice expansion over the recent historical period (Beadling et al., 2020; Roach et al., 2020; Wills et al., 2022), leading to large uncertainty in projections of future Antarctic and Southern Ocean change (Fox‐Kemper et al., 2021). Southern Ocean SSTs and Antarctic sea ice are tightly coupled (Blanchard‐Wrigglesworth et al., 2021; X. Zhang et al., 2021). In CMIP6 models, the Southern Ocean is typically biased warm and fresh relative to observations, with some models being exceptionally warm (Beadling et al., 2020).…”
Section: Introductionmentioning
confidence: 99%